ANALYSIS OF CONSTRUCTIONS OF HARVESTERS AND COMBINE HARVESTER ADD-ON DEVICES AND THEIR USAGE PATTERN SOYBEAN AND RAPE HARVESTING - Іванишин, В. В.; Іліяшик, В. В.; Дуганець, В. I. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The issues devoted to soybean and rape harvesting technologies are highlighted in the study. The analysis of specific reapers such as Flex and rape combine harvester add-on devices produced by John Deere; CLAAS; New Holland companies is given in the study. The constructive and technological characteristics of Flex reapers; which make it possible to collect soybeans; peas at the lowest cutting height and combine harvester add-on devices with minimal loss were examined in the article. The features of flexible platforms and flexible cutting machines to special reapers of combine harvesters were considered in the study. The analysis of reaper and add-on combine harvester device constructions showed that it is possible to adopt them to CLAAS TUCANO; LEXION combine harvesters. The analysis of John Deere 630F; 635F HidroFlex reaper constructions and PZR add-on devices in combination with CLAAS TUCANO; LEXION combine harvesters shows positive results; high quality and availability.